Implementasi E-Kios Dalam Mempercepat Pelayanan Publik Sebagai Inovasi Pemerintah Di Kelurahan Pradah Kalikendal Kota Surabaya - Diffa Adristii Efelian Feblianto; Djoko Widodo (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2024)
The application of E-Kios as a form of population administration service innovation which aims to make it easier for the public to carry out population administration requests is still not optimal due to problems with internal and external factors, for internal factors this service is carried out directly on the service destination website, not through the E-Kios website and in the environment. External E-Kios communication is still not running well because it only relies on poster stand displays in sub-districts, sub-district health centers and RW halls. The implementation of E-Kiosks uses Edward III's Implementation theory, namely: communication, resources, disposition and bureaucratic structure so that services using E-kiosks can be easily noticed and used effectively.